Analisis Konsep Sistem Operasional Landasan Hukum Dan Jenis Lembaga Jasa Keuangan Khusus di Indonesia - Gamal Fadilah; Eka Widiya Fradinda; M. Sakhi Awwah (Jurnal Ekonomi Syariah Pelita Bangsa, 2026)
The study aims to explain the basic concept of LJKK, its differences from conventional financial institutions, its operational systems, and the legal framework governing its activities. The research method uses a descriptive approach through literature review enriched by field observations and interviews with PNM. The results indicate that PNM plays a strategic role in empowering micro-enterprises, particularly underprivileged women, through collateral-free financing, group mechanisms, and business mentoring. PNM's operations are also supported by digital risk assessment (CCM) technology and intensive post-disbursement field supervision. The legal analysis reveals several regulatory gaps, particularly regarding the legality of joint liability mechanisms, algorithmic accountability, and consumer protection for vulnerable groups. Overall, the empirical findings on PNM demonstrate how LJKK functions not only as a financing institution but also as a development instrument capable of reaching sectors not served by conventional financial institutions.